Health literacy and strategies of behavioral change for the COVID - 19 confrontation - Rolando Bonal Ruiz; Raúl Leyva Caballero; Ana Hortensia Rodríguez Espinosa (Centro Provincial de Información de Ciencias Médicas, 2021)
The environmental, social and systemic interventions are not enough to reduce the transmission of coronavirus, but it is important to act on the individuals behavior, a factor that favors the transmission. The use of effective mechanisms of information, education and communication is necessary, based on health literacy in a critical way and with basic principles of behavior changes. These approaches, not usually implemented, go beyond the simple information and health education, because they should be carried out not only by health professionals but also by all the influential people in the population. The functioning of the behavior change principles and their implementation in the COVID - 19 confrontation stage are explained and some digital links on how to proceed in health literacy are shown.